Silicon-based negative electrode material and preparation method and application thereof
By using multi-layer cladding structure and cross-linking technology in the silicon-based negative electrode material, the problem of volume expansion of the silicon-based negative electrode material during circulation is solved, and the mechanical strength and battery performance are improved.
Patent Information
- Application Number
- CN202411582584.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
AI Technical Summary
The volume expansion of the silicon-based negative electrode material during the circulation process is severe, resulting in a decrease in mechanical strength, affecting the energy density, rate performance and circulation performance of lithium-ion batteries.
By adopting a multi-layer cladding structure in the silicon-based negative electrode material, including the silicon-based material core, graphene oxide cladding and crosslinking material cladding, the crosslinking and hydrogen bonding physics of conductive polymers and flexible polymer materials are used to utilize the cross-linking and hydrogen bonding physics of conductive polymers and flexible polymer materials. Self-crosslinking, forming a three-dimensional porous structure to inhibit volume expansion and increase mechanical strength.
It effectively suppresses the volume expansion of silicon-based materials, improves mechanical strength, and improves the energy density, rate performance and cycling performance of lithium-ion batteries.
Smart Images

Figure CN119419252A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] The exhaust gas released during the combustion of traditional fossil fuels will damage the ecology and endanger human health. Lithium-ion batteries have developed rapidly in recent years due to their high energy density, long cycle life, clean and environmentally friendly, and portable advantages. They have been widely used in electronic products such as mobile phones and laptops. With the rapid development of new energy, people pay more attention to the energy storage capacity of lithium-ion batteries. At present, improving the capacity of lithium-ion batteries has become one of the research hotspots.
[0003] Traditional lithium-ion batteries use graphite as the negative electrode, but its capacity is only 372mAh / g, while the theoretical capacity of batteries using silicon-based materials as negative electrodes is 4200mAh / g, which is more than 10 times the capacity of traditional graphite negative electrodes. At the same time, silicon is abundant in nature and is cheap and easy to obtain. The above advantages make silicon-based materials one of the most promising negative electrode materials. Silicon materials are different from graphite and lithium ion embedded in the form of alloys (Li 22 Si5). This combination gives it an extremely high theoretical capacity, but it also brings huge challenges. The main reasons are as follows: First, the conductivity of the silicon negative electrode itself is poor, only 2.52×10 -4 S / cm, which affects the transmission of lithium ions, thereby weakening the cycle performance and rate performance of lithium-ion batteries; secondly, the silicon negative electrode will produce a huge volume expansion during the cycle, and its expansion rate can reach 300%, which has also become the most important reason for limiting the commercial use of silicon negative electrodes. The huge volume expansion causes the silicon particles to pulverize or rupture, thereby peeling off from the current collector, losing electrical contact, and severely attenuating the capacity; thirdly, during the first cycle of charge and discharge, the electrode surface contacts the electrolyte to form a layer of solid electrolyte membrane, also known as SEI membrane. The formation of SEI membrane will consume some lithium ions from the positive electrode, and this consumption is irreversible, resulting in low coulomb efficiency in the first cycle and reducing the capacity of lithium-ion batteries. In the subsequent cycle process, due to the continuous expansion and rupture of silicon particles, the SEI membrane will rupture accordingly, and the exposed silicon particles will contact the electrolyte to continuously form a new SEI membrane, causing the SEI layer to continue to thicken, affecting the transmission of ions.
[0004] Therefore, how to optimize the silicon-based negative electrode, alleviate volume expansion and improve the mechanical strength of silicon-based materials is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a silicon-based negative electrode material and a preparation method and application thereof. The silicon-based negative electrode material provided by the present invention, through the coordinated cooperation of various coating layer materials and coating sequence, not only effectively suppresses the volume expansion of the silicon-based material core, but also improves the mechanical strength of the silicon-based negative electrode material, thereby improving the energy density, rate performance and cycle performance of the battery.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a silicon-based negative electrode material, which includes, from the inside to the outside, a silicon-based material core, a graphene oxide coating layer and a cross-linked coating layer; the cross-linked coating layer includes a cross-linked product of a conductive polymer material and a flexible polymer material, and the flexible polymer material also includes hydrogen bond physical self-crosslinking.
[0008] The silicon-based negative electrode material provided by the present invention suppresses the excessive volume expansion of the silicon-based material core during the charge and discharge process through the coordinated cooperation of various coating layer materials and the coating sequence, and the cross-linked product has a three-dimensional porous structure, which not only reserves expansion space for the internal stress caused by the volume expansion and contraction of the silicon-based material core during the charge and discharge process, but also provides a loose channel for the transmission of lithium ions; at the same time, the physical self-crosslinking of hydrogen bonds between the conductive polymer and the flexible polymer material itself realizes the improvement of the mechanical strength of the silicon-based negative electrode material, thereby providing favorable support for the belt-walking preparation of self-supporting negative electrode sheets, and improving the energy density, rate performance and cycle performance of the battery.
[0009] In the present invention, the coordinated cooperation of each coating layer material and the coating sequence are indispensable. At the same time, if there is no physical self-crosslinking of hydrogen bonds between the flexible polymer materials in the cross-linked coating, continuous belt-type production cannot be achieved, and the mechanical strength of the silicon-based material cannot be improved.
[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0011] Preferably, the graphene in the graphene oxide coating layer comprises reduced graphene oxide.
[0012] Preferably, the conductive polymer material and the flexible polymer material are cross-linked and bonded via dynamic borate ester bonds.
[0013] In the present invention, the conductive polymer material and the flexible polymer material are cross-linked by dynamic borate bonds, so that the conductive polymer material and the flexible polymer material are cross-linked by chemical bonds, thereby obtaining a three-dimensional porous conductive network structure, which has more advantages in electron and ion transmission and structural stability, and the dynamic borate bonds can be broken and recombined during the charge and discharge process. The hydrogen bonding between the flexible polymers further enhances the mechanical properties and structural stability of the conductive network.
[0014] Preferably, the conductive polymer material contains an amino group, and the conductive polymer material includes any one of polyaniline and / or polyphenylene diamine, or a combination of at least two of them.
[0015] In the present invention, in addition to the conductive polymer materials provided above, derivatives thereof, such as polyaniline derivatives, etc., may also be included; in addition, in addition to the conductive polymer materials containing an amino matrix, other types of conductive polymer materials, such as polypyrrole or polythiophene, etc., are also applicable to the present invention.
[0016] Preferably, the flexible polymer material contains hydroxyl groups, and the flexible polymer material includes any one of polyvinyl alcohol, polyethylene glycol or sodium alginate, or a combination of at least two of them.
[0017] In the present invention, in addition to the flexible polymer material containing hydroxyl groups, the flexible polymer materials of other groups that can be cross-linked with the conductive polymer material are also applicable to the present invention, such as polyacrylic acid.
[0018] It should be noted that the material in the core of the silicon-based material includes any one of pure silicon material, silicon-carbon material or silicon-oxygen material, or a combination of at least two of them, preferably silicon-oxygen material.
[0019] In the present invention, there is no special limitation on the specific type of material in the core of the silicon-based material, and the present invention is applicable to all silicon-based negative electrode materials with volume expansion problems; further, the use of silicon-oxygen materials as silicon-based particles can better improve the cycle performance.
[0020] In addition, silicon-carbon materials include, but are not limited to, material types of silicon materials deposited inside porous carbon, and material types of silicon materials coated with a carbon coating layer;
[0021] The chemical formula of silicon oxide material is SiO x , wherein 1≤x≤2, for example 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In a second aspect, the present invention provides a method for preparing the silicon-based negative electrode material as described in the first aspect, the preparation method comprising the following steps:
[0023] The intermediate structure is mixed with the cross-linking material raw material, and a first cross-linking coating is performed, and a second cross-linking coating is performed to obtain the silicon-based negative electrode material;
[0024] Wherein, the intermediate structure includes a silicon-based material core and a graphene oxide coating layer.
[0025] The preparation method provided by the present invention realizes the crosslinking of the conductive polymer material and the flexible polymer material through the first crosslinking coating, thereby obtaining a three-dimensional porous conductive network structure coated on the surface of the intermediate structure, improving the mechanical properties of the negative electrode material, and realizing the self-support of the silicon-based negative electrode material; further, through the second crosslinking coating, the hydrogen bond physical self-crosslinking of the flexible polymer material is realized, thereby further improving the mechanical strength, which can not only further inhibit the volume expansion of the silicon-based core and improve the cycle stability of the battery, but also provide the necessary supporting conditions for the belt-walking preparation of the self-supporting negative electrode.
[0026] Preferably, the D50 of the intermediate structure is 50 nm to 5 μm, for example, 50 nm, 100 nm, 500 nm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the cross-linking material raw materials include monomer materials of conductive polymer materials, flexible polymer material solution, cross-linking agent, initiator and solvent.
[0028] It can be understood that the monomer material of the conductive polymer material in the present invention matches the conductive polymer material, for example, it can be aniline monomer, phenylenediamine monomer or pyrrole monomer.
[0029] Preferably, the cross-linking agent comprises aminophenylborate hydrochloride.
[0030] It should be noted that when the cross-linking agent provided by the present invention is selected from the above substances, it is inevitable to add hydrochloric acid as a solvent for the cross-linking agent, and the concentration and amount of hydrochloric acid added can be adaptively selected and adjusted according to the specific amount of cross-linking agent added: for example, hydrochloric acid with a concentration of 6 mol / L can generally be selected.
[0031] Preferably, the mass fraction of the flexible polymer material solution is 9-12%, for example 9%, 9.5%, 10%, 10.5%, 11%, 11.5% or 12%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the mass ratio of the intermediate structure to the monomer material of the conductive polymer material is (1-3):1, for example 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.4:1, 2.5:1, 2.8:1 or 3:1, etc., preferably (1.2-2.4):1, but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0033] Preferably, the molar ratio of the cross-linking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, for example, 0.1:1.5:7.6, 0.11:1.5:7.6, 0.12:1.5:7.6, 0.13:1.5:7.6, 0.135:1.5:7.6, 0.14:1.5:7.6, 0.15:1.5:7.6, 0.16:1.5:7.6, 0.17:1.5:7.6, 0.18:1.5:7.6, 0.18:1.5:7.6 or 0.2:1.5:7.6, etc., preferably (0.11-0.135):1.5:7.6, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the temperature of the first cross-linking coating is -20 to 0°C, for example, -20°C, -18°C, -15°C, -13°C, -10°C, -8°C, -5°C, -3°C, -1°C or 0°C.
[0035] Preferably, the first cross-linking coating time is 4 to 12 hours, for example 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the second cross-linking coating method comprises freeze-thaw cycle treatment.
[0037] In the present invention, the freeze-thaw cycle method can be used to better obtain the product of physical cross-linking between flexible polymers, further inhibit the volume expansion of the silicon-based core during the charge and discharge process, improve the structural stability and mechanical properties of the material, and realize continuous tape production.
[0038] Preferably, during the freeze-thaw cycle, the freezing temperature is -25 to -15°C, such as -15°C, -20°C or -25°C, and the melting temperature range is 25 to 30°C, such as 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, the duration of each freeze-thaw cycle is 4 to 12 h, for example, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h.
[0040] It should be noted that the so-called freeze-thaw cycle in the present invention is the time for a complete freeze-thaw process.
[0041] Preferably, the freeze-thaw cycle treatment is performed 2 to 3 times, for example 2 or 3 times.
[0042] It should also be noted that the present invention does not specifically limit the preparation method of the intermediate structure, and the present invention is applicable to any method of coating a silicon-based material core with graphene oxide that can be known within a reasonable range by a person skilled in the art.
[0043] For example, the silicon-based material and the graphene oxide solution are directly mixed and stirred, and then dried to obtain an intermediate structure; it can also be further preferred that the surface of the silicon-based material core and the graphene oxide coating layer are connected through an aminoamide condensation reaction, and the contact effect between the silicon-based material core and the graphene oxide coating layer is improved through the aminoamide condensation reaction, so that the core and the graphene oxide coating layer are tightly coated, the transmission path of electrons and ions is shortened, and the electrical properties of the material are better improved.
[0044] The method for preparing the intermediate structure of the above-mentioned specific aminoamide condensation reaction connection mode comprises the following steps:
[0045] The silicon-based material with amino groups on the surface, the condensation agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and the graphene oxide solution with carboxyl groups on the surface are mixed, stirred and coated, and after drying, reduction heat treatment is performed to obtain an intermediate structure.
[0046] Exemplarily, the present invention also provides a method for modifying the surface of a silicon-based material with amino groups: a silane coupling agent method.
[0047] Exemplarily, the present invention also provides a method for modifying the surface of graphene oxide with carboxyl groups:
[0048] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added to the graphene oxide solution at a molar ratio of 1:1, and stirred at room temperature to activate the carboxyl groups.
[0049] Optionally, the solution after the first mixing is subjected to solid-liquid separation (such as centrifugation), washed (such as water washing and alcohol washing), and then dried (the drying method includes freeze drying).
[0050] Optionally, the mass ratio of the silicon-based material to the graphene oxide is adjusted to 10:(0.4-0.6), for example, 10:0.4, 10:0.5 or 10:0.6, etc. The temperature of the reduction heat treatment in the present invention is 800-1200, for example, 800°C, 900°C, 1000°C, 1100°C or 1200°C, etc., and the time of the reduction heat treatment is 2-5h, for example, 2h, 3h, 4h or 5h, etc.
[0051] In a third aspect, the present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the silicon-based negative electrode material as described in the first aspect or the negative electrode material prepared by the preparation method as described in the second aspect.
[0052] In a fourth aspect, the present invention provides a self-supporting negative electrode plate, wherein the self-supporting negative electrode plate is composed of the silicon-based negative electrode material as described in the first aspect.
[0053] The self-supporting negative electrode plate provided by the present invention adopts the silicon-based negative electrode material provided by the first aspect, does not require a current collector as a support, and does not require the addition of an additional binder, thereby effectively improving the energy density of the battery; at the same time, under the synergistic effect of chemical cross-linking and hydrogen bond physical connection, it can be prepared by a slurry coating preparation method, thereby realizing a continuous belt-type production method for the self-supporting negative electrode plate, and can also accurately control the surface density and thickness of the coated negative electrode plate; thereby, the self-supporting negative electrode plate has excellent energy density, rate performance and cycle performance.
[0054] In the present invention, if the silicon-based negative electrode material does not contain physical self-crosslinking of hydrogen bonds between flexible polymer materials, the mechanical strength of the self-supporting negative electrode plate is difficult to ensure, and it is also impossible to achieve slurry coating production, which is inefficient and cannot be mass-produced.
[0055] In a fifth aspect, the present invention provides a method for preparing the self-supporting negative electrode sheet as described in the fourth aspect, the preparation method comprising the following steps:
[0056] Mixing the intermediate structure and the raw materials of the cross-linked coating layer to obtain a negative electrode slurry;
[0057] The negative electrode slurry is coated on the surface of the base film, cross-linked and polymerized once, and cross-linked twice to obtain a self-supporting negative electrode sheet loaded on the surface of the base film, and the self-supporting negative electrode is obtained after peeling;
[0058] Wherein, the intermediate structure includes a silicon-based material core and a graphene oxide coating layer.
[0059] The preparation method provided by the present invention can prepare a self-supporting negative electrode plate by a slurry coating method, and can realize a continuous tape-walking production process on the surface of a conventional base film. The surface density of the active material can be controlled by controlling the coating thickness, and the transmission distance of lithium ions can be reduced by regulating the coating thickness, thereby preparing a high-rate self-supporting three-dimensional porous silicon-based negative electrode plate.
[0060] Preferably, the raw materials of the cross-linked coating layer include monomer materials of conductive polymer materials, flexible polymer material solution, a cross-linking agent, an initiator and a solvent.
[0061] Preferably, the mass fraction of the flexible polymer material solution is 9-12%, for example 9%, 9.5%, 10%, 10.5%, 11%, 11.5% or 12%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] Preferably, the mass ratio of the intermediate structure to the monomer material of the conductive polymer material is (1-3):1, for example, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.4:1, 2.5:1, 2.8:1 or 3:1, etc., preferably (1.2-2.4):1, preferably (1.2-2.4):1.
[0063] Preferably, the molar ratio of the cross-linking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, for example, 0.1:1.5:7.6, 0.11:1.5:7.6, 0.12:1.5:7.6, 0.13:1.5:7.6, 0.135:1.5:7.6, 0.14:1.5:7.6, 0.15:1.5:7.6, 0.16:1.5:7.6, 0.17:1.5:7.6, 0.18:1.5:7.6, 0.18:1.5:7.6 or 0.2:1.5:7.6, etc., preferably (0.11-0.135):1.5:7.6, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0064] Preferably, the coating has a thickness of 150 to 1000 μm, for example, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, 850 μm, 900 μm, 950 μm or 1000 μm, etc.
[0065] In the present invention, by adjusting the coating thickness to 150-1000 μm, the surface density is further adjusted. The thin coating can reduce the Li+ The diffusion distance is reduced, thus obtaining a negative electrode structure with excellent rate performance.
[0066] Preferably, the temperature of the primary cross-linking polymerization is -20 to 0°C, for example, -20°C, -18°C, -15°C, -13°C, -10°C, -8°C, -5°C, -3°C, -1°C or 0°C.
[0067] Preferably, the time for the primary cross-linking polymerization is 4 to 12 h, for example 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] Preferably, the secondary cross-linking method comprises freeze-thaw cycle treatment.
[0069] In the preparation process of the self-supporting negative electrode sheet of the present invention, the freeze-thaw cycle treatment method can better realize the cross-linking of physical hydrogen bonds between flexible polymers, form a second coating network, further limit the volume expansion of the silicon-based core during the charge and discharge process, improve the structural stability and mechanical properties of the negative electrode material, and realize continuous belt-type production.
[0070] Preferably, during the freeze-thaw cycle, the freezing temperature is -25 to -15°C, such as -15°C, -20°C or -25°C, and the melting temperature range is 25 to 30°C, such as 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] In the present invention, during the freeze-thaw cycle, the freezing temperature is controlled at -25 to -15°C, and / or the melting temperature is controlled at 25 to 30°C, which can ensure the generation of hydrogen bond physical crosslinking between flexible polymers and avoid the destruction of the primary crosslinked coating structure.
[0072] Preferably, the time for each freeze-thaw cycle is 4 to 12 hours, for example 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0073] Preferably, the freeze-thaw cycle treatment is performed 2 to 3 times, such as 2 times or 3 times.
[0074] In the present invention, the number of freeze-thaw cycle treatments is further adjusted to 2 to 3 times, which is more conducive to the complete physical cross-linking of hydrogen bonds between flexible polymers.
[0075] Furthermore, the type of base film in the present invention is selected by conventional technology, which can realize slurry coating, is resistant to low temperatures and easy to peel off from the coating. The present invention is applicable to all types. The base film includes but is not limited to polypropylene PP, polyethylene PE, polyethylene terephthalate PET, polyimide PI, and polyurethane PU.
[0076] It should be noted that the preparation method of the self-supporting negative electrode plate provided by the present invention, except that the preparation process is slightly different from the preparation process of the silicon-based negative electrode material, the rest of the preparation raw materials, preparation raw materials and specific methods are consistent with the preparation method of the silicon-based negative electrode material; that is, there is a difference between the molding method and the molding process, and the product structure is essentially the same as that of the silicon-based negative electrode material.
[0077] In a sixth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet as described in the third aspect or the self-supporting negative electrode sheet as described in the fourth aspect.
[0078] Compared with the prior art, the present invention has the following beneficial effects:
[0079] (1) The silicon-based negative electrode material provided by the present invention suppresses the excessive volume expansion of the silicon-based material core during the charge and discharge process through the coordinated cooperation of each coating layer material and the coating sequence, and the cross-linked product is a three-dimensional porous structure, which not only reserves expansion space for the internal stress caused by the volume expansion and contraction of the silicon-based material core during the charge and discharge process, but also provides a loose channel for the transmission of lithium ions; at the same time, the physical self-crosslinking of hydrogen bonds between the conductive polymer and the flexible polymer material realizes the improvement of the mechanical strength of the silicon-based negative electrode material, thereby providing favorable support for the preparation of self-supporting negative electrode sheets by walking belt type, and improving the energy density, rate performance and cycle performance of the battery. .
[0080] (2) The preparation method provided by the present invention realizes the cross-linking of the conductive polymer material and the flexible polymer material through the first cross-linking coating, thereby obtaining a three-dimensional porous conductive network structure coated on the surface of the intermediate structure, thereby improving the mechanical properties of the negative electrode material and realizing the self-support of the silicon-based negative electrode material; further, through the second cross-linking coating, the hydrogen bond physical self-cross-linking of the flexible polymer material is realized, thereby further improving the mechanical strength, which can not only further inhibit the volume expansion of the silicon-based core and improve the cycle stability of the battery, but also provide the necessary supporting conditions for the belt-type preparation of the self-supporting negative electrode.
[0081] (3) The self-supporting negative electrode plate provided by the present invention adopts the silicon-based negative electrode material provided by the first aspect, does not require a current collector as a support, and does not require the addition of an additional binder, thereby effectively improving the energy density of the battery; at the same time, under the synergistic effect of chemical cross-linking and hydrogen bond physical connection, it can be prepared by a slurry coating preparation method, thereby realizing a continuous belt-type production method for the self-supporting negative electrode plate, and can also accurately control the surface density and thickness of the coated negative electrode plate; thereby, the self-supporting negative electrode plate has excellent energy density, rate performance and cycle performance.
[0082] (4) The preparation method provided by the present invention can prepare a self-supporting negative electrode plate by a slurry coating method, and can realize a continuous tape-walking production process on the surface of a conventional base film. The surface density of the active material can be controlled by controlling the coating thickness. The transmission distance of lithium ions can be reduced by regulating the coating thickness, thereby preparing a high-rate self-supporting three-dimensional porous silicon-based negative electrode plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 Schematic diagram of the preparation process of the self-supporting negative electrode sheet provided in Example 1. DETAILED DESCRIPTION
[0084] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0085] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0086] In the description of this application, the technical terms "first", "second", "first", "secondary", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0087] Example 1
[0088] The present embodiment provides a self-supporting negative electrode plate, the self-supporting negative electrode plate is composed of a silicon-based negative electrode material, the silicon-based negative electrode material includes a silicon dioxide core, a graphene oxide coating layer and a cross-linked coating layer from the inside to the outside; the cross-linked coating layer includes a cross-linked product of polyaniline and polyvinyl alcohol, and the polyvinyl alcohol further includes hydrogen bond physical self-crosslinking;
[0089] The silicon dioxide core and the reduced graphene oxide coating layer are connected through an aminoamide condensation reaction; polyaniline and polyvinyl alcohol are cross-linked through borate ester bonds to obtain a cross-linked product.
[0090] The preparation method of the self-supporting negative electrode sheet is as follows: Figure 1 As shown:
[0091] (1) adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in a molar ratio of 1:1 to 1000 mL of graphene oxide (0.5 mg / mL) dispersion (aqueous solution), stirring at room temperature for 30 min to activate the carboxyl groups, and obtaining a mixed solution of graphene oxide with surface modified carboxyl groups;
[0092] Then, 10 g of amino-modified silica with a D50 of 100 nm was added to the mixed solution, and stirring was continued at room temperature for 24 h; the mixture was centrifuged for solid-liquid separation, washed with water and methanol, and freeze-dried to obtain a 24-hour graphene oxide-coated silica (GO@SiO2) precursor; the GO@SiO2 precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and the mixture was kept at 1050°C for 3 h, and naturally cooled to room temperature to obtain an intermediate structure rGO@SiO2 powder (D50 of 500 nm) with a reduced graphene oxide-coated silica core;
[0093] (2) Prepare a 9% PVA solution;
[0094] Prepare the substrate solution: dissolve 0.0364 g of aminophenyl boronate (ABA) in 1.67 mL of HCl (6 mol / L), add deionized water and aniline monomer (AN) and mix evenly, add rGO@SiO2 powder and mix evenly, finally add PVA solution, continue stirring and mixing evenly to obtain solution A, and place it in an ice water bath for use. In the substrate solution, the mass ratio of the intermediate structure to the aniline monomer is 2:1, and the molar ratio of ABA, AN and PVA is 0.11:1.5:7.6;
[0095] Prepare initiator solution: Dissolve 6.9 g of ammonium persulfate (APS) solution in 15 mL of deionized water to prepare APS solution, and place in an ice water bath for later use;
[0096] The substrate solution is extrusion coated on a low-temperature resistant polymer film (PET) and the coating surface density is controlled to 180g / m 2(coating thickness is 210 μm), and then carried to a 0°C thermostat to spray ammonium sulfate solution (APS) to initiate polymerization (one-time cross-linking coating), thereby forming a three-dimensional porous negative electrode film on the polymer film; then frozen at -20°C for 4 hours, dissolved at 30°C for 4 hours (freeze-thaw cycle), cycled twice, and then peeled off from the polymer film to form a three-dimensional porous PANI@rGO@SiO2 self-supporting film;
[0097] After peeling, the film is washed in a multi-pass washing tank of deionized water and ethanol to remove impurity ions, cut, and freeze-dried to obtain the self-supporting negative electrode sheet.
[0098] Example 2
[0099] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the intermediate structure (D50 is 1.5 μm) to the aniline monomer is 1.2:1;
[0100] Coating surface density 174g / m 2 (coating thickness is 180 μm), the temperature of the first cross-linking coating is -20°C, and the time of the first cross-linking coating is 8 h; the freeze-thaw cycle is freezing at -10°C for 6 h, thawing at 20°C for 6 h, and the cycle is repeated 3 times.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Example 3
[0103] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the intermediate structure (D50 is 3 μm) to the aniline monomer is 2.4:1;
[0104] Coating surface density 168g / m 2 (coating thickness is 150 μm), the temperature of the first cross-linking coating is -10°C, and the time of the first cross-linking coating is 12 h; the freeze-thaw cycle is freezing at -10°C for 6 h, thawing at 20°C for 6 h, and the cycle is repeated 3 times.
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Example 4
[0107] The difference between this embodiment and embodiment 1 is that the material in the core of this embodiment is nano-silicon material, and the cross-linked product is the chemical cross-link between polythiophene and polyacrylic acid and the physical cross-link between polyacrylic acid itself.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Example 5
[0110] The difference between this embodiment and embodiment 1 is that the number of freeze-thaw cycles in step (2) of this embodiment is 1.
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Example 6
[0113] The difference between this embodiment and embodiment 1 is that the number of freeze-thaw cycles in step (2) of this embodiment is 5 times.
[0114] The rest of the preparation methods and parameters were the same as those in Example 1.
[0115] Example 7
[0116] The difference between this embodiment and embodiment 1 is that during the freeze-thaw cycle in step (2) of this embodiment, the freezing temperature is -30°C.
[0117] The rest of the preparation methods and parameters were the same as those in Example 1.
[0118] Example 8
[0119] The difference between this embodiment and embodiment 1 is that during the freeze-thaw cycle in step (2) of this embodiment, the melting temperature is 40°C.
[0120] The rest of the preparation methods and parameters were the same as those in Example 1.
[0121] Example 9
[0122] The difference between this embodiment 1 and embodiment 1 is that in step (2) of this embodiment, the coating thickness is 100 μm.
[0123] The rest of the preparation methods and parameters were the same as those in Example 1.
[0124] Example 10
[0125] The difference between this embodiment 1 and embodiment 1 is that in step (2) of this embodiment, the coating thickness is 1100 μm.
[0126] The rest of the preparation methods and parameters were the same as those in Example 1.
[0127] Comparative Example 1
[0128] The difference between this comparative example and Example 1 is that the negative electrode sheet of this comparative example does not contain hydrogen bond physical crosslinking;
[0129] In the preparation method, no freeze-thaw cycle treatment is performed.
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 1 is that in this comparative example, there is no cross-linked coating layer;
[0133] In the preparation method, step (2) is not performed;
[0134] The preparation method provided in this comparative example cannot obtain a self-supporting negative electrode sheet. The silicon-based negative electrode material obtained is used to prepare a non-self-supporting negative electrode sheet. The specific preparation method is:
[0135] The silicon-based negative electrode material not containing a cross-linked coating layer in this comparative example was mixed with a conductive agent (Super P) and a binder LA132 (15wt%) in a mass ratio of 80:10:10 to prepare a slurry, the coating gap thickness was adjusted to 150μm, and it was coated on one side on a 6μm thick copper foil, dried in a vacuum oven, and rolled to obtain the negative electrode sheet.
[0136] The rest of the preparation methods and parameters were the same as those in Example 1.
[0137] Comparative Example 3
[0138] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, a freeze-thaw cycle treatment is first performed, and then a cross-linking coating process is performed;
[0139] That is, it is first frozen at -20°C for 4 hours, and then thawed at 30°C for 4 hours (freeze-thaw cycle), and the cycle is repeated twice; then it is conveyed to a 0°C constant temperature box and sprayed with ammonium sulfate solution (APS) to initiate polymerization.
[0140] The rest of the preparation methods and parameters were the same as those in Example 1.
[0141] Comparative Example 4
[0142] The difference between this comparative example and Example 1 is that the silicon-based negative electrode material of this comparative example does not contain a graphene oxide coating layer;
[0143] In the preparation method, the intermediate structure in step (2) is directly replaced by a silicon dioxide material with a D50 of 100 nm.
[0144] The rest of the preparation methods and parameters were the same as those in Example 1.
[0145] The negative electrode sheets provided in Examples 1-10 and Comparative Examples 1-4 were used as negative electrodes, 1 mol / L LiPF6 electrolyte (volume ratio of ethylene carbonate and diethyl carbonate in the solvent = 1:1) was used, a polypropylene microporous membrane was used as a separator (Celgard 2400 purchased from Celgard Company), and a lithium sheet was used as a counter electrode to assemble a button battery.
[0146] The electrochemical performance test of the battery was carried out on the Wuhan Blue Electric Battery Test System. The test conditions were:
[0147] (1) First efficiency performance: The assembled battery was charged at a constant current of 0.5C to a cut-off voltage of 2.5V, then charged at a constant voltage to a cut-off current of 0.01C, and then discharged at a constant current of 0.5C to a cut-off voltage of 0.01V. The discharge capacity was divided by the charge capacity to obtain the first charge and discharge efficiency, referred to as the first efficiency.
[0148] (2) Rate performance: The assembled batteries were tested for first cycle charging capacity under constant current charging conditions of 1C, 2C and 3C.
[0149] (3) Cycle performance: The assembled battery was tested on a battery testing system (Blue Electric Test System) and charged and discharged 200 times at a constant current of 1C in the voltage range of 0.01 to 2.5V under room temperature conditions. The retention rate after 200 cycles was obtained by dividing the 200th charge capacity by the first charge capacity.
[0150] The above test results are shown in Table 1.
[0151] Table 1
[0152]
[0153]
[0154] In summary, the silicon-based negative electrode material provided by the present invention suppresses the excessive volume expansion of the silicon-based material core during the charge and discharge process through the coordinated cooperation of each coating layer material and the coating sequence, and the cross-linked product is a three-dimensional porous structure, which not only reserves expansion space for the internal stress caused by the volume expansion and contraction of the silicon-based material core during the charge and discharge process, but also provides a loose channel for the transmission of lithium ions; at the same time, the physical self-cross-linking of hydrogen bonds between flexible polymer materials also realizes the improvement of the mechanical strength of the silicon-based negative electrode material, thereby providing favorable support for the belt-type preparation of self-supporting negative electrode sheets, and improving the energy density, rate performance and cycle performance of the battery.
[0155] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material includes, from the inside to the outside, a silicon-based material core, a graphene oxide coating layer and a cross-linked coating layer; the cross-linked coating layer includes a cross-linked product of a conductive polymer material and a flexible polymer material, and the flexible polymer material also includes hydrogen bond physical self-crosslinking.
2. The silicon-based negative electrode material according to claim 1, characterized in that: The graphene in the graphene oxide coating layer includes reduced graphene oxide.
3. The silicon-based negative electrode material according to claim 1 or 2, characterized in that: The conductive polymer material and the flexible polymer material are cross-linked and bonded via borate ester bonds; Preferably, the conductive polymer material contains an amino group, and the conductive polymer material includes any one of polyaniline and / or polyphenylene diamine or a combination of at least two thereof; Preferably, the flexible polymer material contains hydroxyl groups, and the flexible polymer material includes any one of polyvinyl alcohol, polyethylene glycol or sodium alginate, or a combination of at least two of them.
4. A method for preparing a silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The intermediate structure is mixed with the cross-linking material raw material, and a first cross-linking coating is performed, and a second cross-linking coating is performed to obtain the silicon-based negative electrode material; Wherein, the intermediate structure includes a silicon-based material core and a graphene oxide coating layer.
5. The preparation method according to claim 4, characterized in that: The D50 of the intermediate structure is 50nm to 5μm; Preferably, the cross-linking material raw materials include monomer materials of conductive polymer materials, flexible polymer material solution, cross-linking agent, initiator and solvent; Preferably, the cross-linking agent comprises aminophenylborate hydrochloride; Preferably, the mass fraction of the flexible polymer material solution is 9-12%; Preferably, the mass ratio of the intermediate structure to the monomer material of the conductive polymer material is (1-3):1, preferably (1.2-2.4):1; Preferably, the molar ratio of the crosslinking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, preferably (0.11-0.135):1.5:7.6; Preferably, the temperature of the first cross-linking coating is -20 to 0°C, and the time of the first cross-linking coating is 4 to 12 hours; Preferably, the second cross-linking coating method includes freeze-thaw cycle treatment; Preferably, during the freeze-thaw cycle, the freezing temperature is -25 to -15°C, and the melting temperature range is 25 to 30°C; Preferably, the time of each freeze-thaw cycle is 4 to 12 hours; Preferably, the freeze-thaw cycle treatment is performed 2 to 3 times.
6. A negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, and the negative electrode active material layer includes the silicon-based negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared by the preparation method according to claim 4 or 5.
7. A self-supporting negative electrode sheet, characterized in that: The self-supporting negative electrode plate is composed of the silicon-based negative electrode material as described in any one of claims 1-3.
8. A method for preparing a self-supporting negative electrode sheet as claimed in claim 7, characterized in that: The preparation method comprises the following steps: Mixing the intermediate structure and the raw materials of the cross-linked coating layer to obtain a negative electrode slurry; The negative electrode slurry is coated on the surface of the base film, cross-linked and polymerized once, and cross-linked twice to obtain a self-supporting negative electrode sheet loaded on the surface of the base film, and the self-supporting negative electrode is obtained after peeling; Wherein, the intermediate structure includes a silicon-based material core and a graphene oxide coating layer.
9. The preparation method according to claim 8, characterized in that: The raw materials of the cross-linked coating layer include monomer materials of conductive polymer materials, flexible polymer material solution, cross-linking agent, initiator and solvent; Preferably, the mass fraction of the flexible polymer material solution is 9-12%; Preferably, the mass ratio of the intermediate structure to the monomer material of the conductive polymer material is (1-3):1, preferably (1.2-2.4):1; Preferably, the molar ratio of the crosslinking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, preferably (0.11-0.135):1.5:7.6; Preferably, the coating has a thickness of 150 to 1000 μm; Preferably, the temperature of the primary cross-linking polymerization is -20 to 0°C, and the time of the primary cross-linking polymerization is 4 to 12 hours; Preferably, the secondary cross-linking method comprises freeze-thaw cycle treatment; Preferably, during the freeze-thaw cycle, the freezing temperature is -25 to -15°C, and the melting temperature range is 25 to 30°C; Preferably, the time of each freeze-thaw cycle is 4 to 12 hours; Preferably, the freeze-thaw cycle treatment is performed 2 to 3 times.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 6 or the self-supporting negative electrode sheet as claimed in claim 7.